English language needs in the Telecommunication, Technology and Media industry : compatibility of employers' and students' expectations - Mechraoui, Khedidja Kaouter (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
Many Employers in Malaysia are not satisfied with graduates' employability skills, especially their English language skills. For this reason, higher education institutions in Malaysia have introduced various English for Occupational Purposes (EOP) courses as well as programmes, which combine academic competencies and practical industry skills. Hence, there is a need to conduct a comprehensive needs analysis in order to reveal the current perceptions of both academia and industry. This study presents an analysis of the English language needs and expectations as perceived by employers in the Telecommunication, Technology and Media industry and students from the Kulliyyah of Information and Communication Technology (ICT), and the Department of English Language and Literature (DELL). The aim of this study was twofold. Firstly, it intended to examine the English language expectations of employers and students. Secondly, it investigated the compatibility of these English language needs and expectations. A convergent parallel mixed method design was deemed to be the most appropriate for this research; it combined qualitative and quantitative approaches. To collect data from the stakeholders, questionnaires, interviews and tests were utilised. The findings revealed that English language proficiency is considered crucial in the workplace, in most cases, more than technical, occupational or academic knowledge. Moreover, both Employers and students accentuated the importance of productive skills: writing and speaking. Moreover, employers suggested that students and universities should develop students' (their) English language skills. Employers also proposed that students develop their communicative competence and ability to increase chances of employability. It was also revealed that students were well aware that being proficient in English is a highly valued asset, which leads to their employability. Overall, the findings disclosed a general compatibility between employers and student's perspectives, which indicates that the academia –industry gap has converged in the recent years due to continuous efforts from both higher education Institutes (HEIs) and employers to increase competent graduates for the workplace.